2014
DOI: 10.1007/s13277-014-2821-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the receptor for advanced glycation end-products and glyoxalase I in patients with renal cancer

Abstract: The receptor for advanced glycation end products (RAGE) and its ligands are involved in the pathogenesis of cancer. Glyoxalase I (GLO1) is an enzyme which detoxifies advanced glycation end product (AGE) precursors. The aim of the study was to find out the relationship between four polymorphisms (single nucleotide polymorphism, SNP) of the RAGE gene (AGER) and one SNP of the GLO1 gene and clear cell renal cancer (ccRCC). All polymorphisms (rs1800625 RAGE -429T/C, rs1800624 -374T/A, rs3134940 2184A/G, rs2070600 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…No difference in allelic and genotype frequencies of glyoxalase I gene was found in patients with pancreatic cancer 39 . Very recently in a large study, Ala111Glu glyoxalase polymorphism was shown to be associated with clear cell renal cancer and RAGE polymorphisms (-429T/C and 2184A/G) with its aggressiveness 40 . The role of glyoxalase gene polymorphisms in cancer thus remain uncertain, but impaired glyoxalase activity may be associated with clear cell renal cancer and with outcome in breast cancer.…”
Section: Ages Their Metabolism and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…No difference in allelic and genotype frequencies of glyoxalase I gene was found in patients with pancreatic cancer 39 . Very recently in a large study, Ala111Glu glyoxalase polymorphism was shown to be associated with clear cell renal cancer and RAGE polymorphisms (-429T/C and 2184A/G) with its aggressiveness 40 . The role of glyoxalase gene polymorphisms in cancer thus remain uncertain, but impaired glyoxalase activity may be associated with clear cell renal cancer and with outcome in breast cancer.…”
Section: Ages Their Metabolism and Cancermentioning
confidence: 99%
“…23,24,39,57,61 ) Kidney cancer EN-RAGE related to obesity status in renal cancer, upregulated in tumor tissue of clear cell renal cancer, especially in pts with poorer overall survival and related to obesity status, Ala111Glu polymorphism linked to clear cell renal cancer (ref. 40,71 )…”
Section: Hmgb1 and Cancermentioning
confidence: 99%
“…More than 30 gene polymorphisms in RAGE have been identified in multiple cancers, including renal caner, oral cancer, breast cancer, colorectal cancer, lung cancer, ovarian cancer, pancreatic cancer, nasopharyngeal carcinoma, and gastric cancer (Cheng et al, 2005; Chocholaty et al, 2014; Gu et al, 2008; Krechler et al, 2010; Pan et al, 2013; Qian, Sun, Zhang, Ke, & Zhu, 2014; Su, Chien, Lin, Chen, & Yang, 2015; Zhang et al, 2013; Zhou, Deng, Li, Yin, & Ye, 2014). A comprehensive meta-analysis suggested that the 82G/S polymorphism (3374 cancer cases vs. 3757 controls) in the RAGE promoter region is associated with a significantly increased risk of cancer, where −374T/A polymorphism (2936 cancer cases vs. 3,338 control) is associated with a reduced risk of cancer (Xia et al, 2015).…”
Section: Scavenger Receptors In Cancer Immunobiologymentioning
confidence: 99%
“…Moreover, it was suggested that Glo1 might represent a useful target for therapy in cancers with Glo1 amplification, as RCa. As to studies on the association of Glo1 A111E polymorphism with the risk of RCa, they have been limited to only one study in a cohort of 214 patients with CCA [71]. This study demonstrated the link of E111A (419A/C) Glo1 SNP to the presence of CCR.…”
Section: Glo1mentioning
confidence: 78%